(untitled) (Genius Repository, 2023)
This article delves into diverse and innovative methods employed in the formation of speech activity among preschool children. It explores the role of play-based learning, parental involvement, early intervention, holistic speech activities, and the celebration of progress. The article emphasizes the importance of a collaborative approach involving educators, parents, and speech therapists in nurturing confident communicators during early childhood education.